Negotiating Risks and Responsibilities During Lockdown: Ethical Reasoning and Affective Experience in Aotearoa New Zealand - Trnka, Susanna; Long, Nicholas; Aikman, Pounamu; Appleton, Nayantara; Davies, Sharyn; Deckert, Antje; Fehoko, Edmond; Holroyd, Eleanor; Jivraj, Naseem; Laws, Megan; Martin-Anatias, Nelly; Roguski, Michael; et al. (Informa UK Limited, 2021)
Over forty-nine days of Level 4 and Level 3 lockdown, residents of Aotearoa New Zealand were subject to ‘stay home’ regulations that restricted physical contact to members of the same social ‘bubble’. This article examines their moral decision-making and affective experiences of lockdown, especially when faced with competing responsibilities to adhere to public health regulations, but also to care for themselves or provide support to people outside their bubbles. Our respondents engaged in independent risk assessment, weighing up how best to uphold the ‘spirit’ of the lockdown even when contravening lockdown regulations; their decisions could, however, lead to acute social rifts. Some respondents – such as those in flatshares and shared childcare arrangements – recounted feeling disempowered from participating in the collective management of risk and responsibility within their bubbles, while essential workers found that anxieties about their workplace exposure to the coronavirus could prevent them from expanding their bubbles in ways they might have liked. The inability to adequately care for oneself or for others thus emerges as a crucial axis of disadvantage, specific to times of lockdown. Policy recommendations regarding lockdown regulations are provided.
Keywords: Aotearoa; Collective responsibility; COVID-19; Ethical reasoning; Lockdown; Moral experience; New Zealand; Pandemics; Risk